Enantioselective Carbene Cascade: An Effective Approach to Cyclopentadienes and Applications in Diels–Alder Reactions. Issue 10 (15th April 2016) - Wang, Xiangbo; Zhou, Yunfei; Qiu, Lihua; Yao, Ruwei; Zheng, Yang; Zhang, Cheng; Bao, Xiaoguang; Xu, Xinfang
Abstract: An asymmetric carbene cascade reaction, which proceeds through carbene/alkyne metathesis and formal (3+2) cycloaddition and converts alkynyl‐tethered enol diazoacetates to chiral bicyclic cyclopentadienes, is presented; and no catalytic asymmetric version of these carbene cascade transformations has been disclosed so far. The proton signals of the cyclopropene intermediates are observed in the mechanism study, which clearly demonstrate the reaction pathways. In addition, these products are intercepted via Diels–Alder reactions to provide bridged polycyclic structures in high yields and enantioselectivities. Abstract :